Effect of self-esteem on social interactions during the Ultimatum Game. (June 2017) - Paz, V.; Nicolaisen-Sobesky, E.; Collado, E.; Horta, S.; Rey, C.; Rivero, M.; Berriolo, P.; Díaz, M.; Otón, M.; Pérez, A.; Fernández-Theoduloz, G.; Cabana, Á.; et al.
Abstract: Self-esteem is an attitude formed by self-evaluation based on positive and negative aspects of oneself. Low self-esteem is a risk factor for psychiatric disorders and is especially associated with social difficulties. Recently, behavioral economics has allowed the quantitative study of social interactions. We investigated the association between self-esteem and interpersonal problems and whether self-esteem modulates behavior and emotions during an economic task, the Ultimatum Game (UG). In this task participants accept or reject fair/unfair monetary offers from others. Low (LSE, n=40) and high (HSE, n=45) self-esteem participants were assessed in their interpersonal problems and psychiatric symptoms using self-reported questionnaires, and were compared on their decision making and emotional response during the UG. LSE was associated with depression and anxiety symptoms. In addition, LSE was associated with interpersonal problems, especially in the domains of socially inhibited, nonassertive, overly accommodating, self-sacrificing and cold/distant. During the UG, LSE women reported more anger towards unfair offers than HSE women. Our findings suggest that low self-esteem individuals experience high distress by interpersonal problems in several domains. Importantly, low self-esteem in women seems to be associated with an accentuated emotional response to unfair social exchanges. These results may contribute to treat social difficulties in this population. Highlights: The effect of self-esteem during the Ultimatum Game was investigated. Low self-esteem people experience a high distress by interpersonal problems. Self-esteem modulates anger response to unfair offers in women.